Optimal Food Price Stabilization in a Small Open Developing Country - Gouel, Christophe (Oxford University Press on behalf of the World Bank, 2016)
This paper analyzes the use of storage and trade policies to achieve food price stabilization in a small open developing country. Optimal stabilization policies are identified using a rational expectations storage model with risk-averse consumers and incomplete markets. Without public intervention, price dynamics are driven by domestic productive shocks and international prices. On its own, an optimal storage policy is found to be detrimental to consumers because its stabilizing benefits leak to the world market. In contrast, an optimal combination of storage and trade policies results in a powerful stabilization of domestic food prices. However, such an optimal combination is shown to entail two serious drawbacks: its distributive impacts are large compared to its efficiency benefits, and by distorting excess supply curves, it may aggravate high world price episodes.